TI_GERICHTE 50.2005.22 vom 13. November 2006 , Esproprio parziale di un terreno a lago. Ammontare dell'indennità - TI Tribunale d'appello (2006)
Esproprio parziale di un terreno a lago. Ammontare dell'indennità